Application of Kappa-Carrageenan in the Removal of Methylene Blue by Polymer-Enhanced Ultrafiltration Technique - Boulett-Neira, A; Boulett-Neira, A (Elsevier B.V., 2025)
In this research work, methylene blue (MB) removal from aqueous solutions was performed by polymer enhanced ultrafiltration (PEUF) with the soluble biopolymer Kappa-Carrageenan (KC). The chemical and molecular structure of KC was verified through the vibrational displacement of specific functional groups in the Fourier transform infrared spectroscopy (FT-IR). The content of 20.7 mmol of sulfate groups per gram of KC and a pKa equal to 2.22 were revealed by acid-base titration. This evidenced the strong acidic character of KC and its ability to attract cationic dyes from aqueous solutions. Almost 100 % of MB was removed from water independent of pH and initial MB concentration. Without the need for pH adjustment (5.10), the washing method allowed 2500 mg L−1 of KC to capture up to 399.67 mg g−1 of MB at a concentration of 500 mg L−1. KC in the PEUF process allowed a high effectiveness and efficiency of MB removal in the presence of interferents and in simulated textile waste (98.4 %). Also, its reuse up to four consecutive cycles. Through the enrichment method, a maximum capture capacity of 39 g g−1 was shown in solutions with an initial concentration of 100 mg L−1 of MB without pH adjustment. © 2025 Elsevier B.V.